2011
DOI: 10.3748/wjg.v17.i17.2206
|View full text |Cite
|
Sign up to set email alerts
|

Value of transient elastography for the prediction of variceal bleeding

Abstract: LS measurement by means of TE is a reliable noninvasive method for the detection of EV and for the prediction of variceal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 16 publications
3
15
0
1
Order By: Relevance
“…In agreement with our results Sporea I et al, [19] studied 1000 patients with TE and showed more or less equivalent cut off values (For the presence of varices, the optimal Fibroscan cut-off was 31 kPa and for bleeding cut-off was 50.7 KPa), according to Lebrec [20]; the larger the size of varices the higher risk of bleeding and according to Sporea [19] study cut off value for TE to predict risk of bleeding could be considered as cut off value for prediction of large varices. Moreover, studies carried out by Vizzutti et al, [21] a cutoff value for prediction of varices was 17.6 kPa, these cut off values are smaller than we obtained, but the different demographics and patients characteristics as well as the type of fibroscan machines could be the reason for these discrepancy.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our results Sporea I et al, [19] studied 1000 patients with TE and showed more or less equivalent cut off values (For the presence of varices, the optimal Fibroscan cut-off was 31 kPa and for bleeding cut-off was 50.7 KPa), according to Lebrec [20]; the larger the size of varices the higher risk of bleeding and according to Sporea [19] study cut off value for TE to predict risk of bleeding could be considered as cut off value for prediction of large varices. Moreover, studies carried out by Vizzutti et al, [21] a cutoff value for prediction of varices was 17.6 kPa, these cut off values are smaller than we obtained, but the different demographics and patients characteristics as well as the type of fibroscan machines could be the reason for these discrepancy.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, in clinical practice TE is increasingly used as a rapid and non-invasive and easy repeatable tool to assess liver fibrosis (9)(10)(11)(12)(13)(14) and portal hypertension (15)(16)(17)(18)(19) in various aetiologies of CLD. Furthermore, TE may be used to estimate prognosis (20)(21)(22) or to predict the presence of gastroesophageal varices (23,24). Previous studies showed that several factors, such as sex (25), levels of aminotransferases (26,27), histological necroinflammation (28,29), extrahepatic cholestasis (30,31), liver steatosis (28,(32)(33)(34), body mass index (BMI) (35,36), fasting state (37,38) and central venous pressure (39) might all influence results of TE measurements.…”
mentioning
confidence: 99%
“…Liver fibrosis and GEV have a strong correlation. Many reports to date have described the utility of serum fibrosis markers or imaging techniques in estimating GEV [24][25][26][27][28]. Although serum markers, including the FIB-4 index, APRI, platelet count, and AAR, are simple, the diagnostic accuracy in estimating GEV is not sufficient [29].…”
Section: Discussionmentioning
confidence: 99%